2004
DOI: 10.1074/mcp.m300076-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuropeptides from the Sinus Gland of the Crayfish Orconectes limosus Using Nanoscale On-line Liquid Chromatography Tandem Mass Spectrometry

Abstract: In this article, a novel and sensitive analytical strategy for direct characterization of neuropeptides from the X-Organ-sinus gland neurosecretory system of the crayfish Orconectes limosus is presented. A desalted extract corresponding to 0.5 sinus gland equivalents was analyzed in a nanoflow liquid chromatography system coupled to quadrupole time-of-flight tandem mass spectrometry (nanoLC-QTOF MS/MS). The existence and structural identity of four crustacean hyperglycemic hormone precursor-related peptide var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…These are neurons with T-shaped branches that, together with several other PDH-ir cell groups, form a prominent tract system predominantly in the medulla terminalis, which also contains axons connecting to the brain and to the contralateral eyestalks (arrows in Figure 4A,B) (138,140,141). Since the origins of up to three different identified PDH-isoforms in sinus glands are still not clear (140,211), this problem presents a further complication in the analysis of all these groups of PDH-neurons and for the analysis of possible physiological effects of these hormonally released PDH-isoforms. There is also evidence that these PDH-isoforms are differentially distributed in visual eyestalk ganglia (e.g.…”
Section: Crustacean Hyperglycaemic Hormone (Chh)mentioning
confidence: 99%
See 1 more Smart Citation
“…These are neurons with T-shaped branches that, together with several other PDH-ir cell groups, form a prominent tract system predominantly in the medulla terminalis, which also contains axons connecting to the brain and to the contralateral eyestalks (arrows in Figure 4A,B) (138,140,141). Since the origins of up to three different identified PDH-isoforms in sinus glands are still not clear (140,211), this problem presents a further complication in the analysis of all these groups of PDH-neurons and for the analysis of possible physiological effects of these hormonally released PDH-isoforms. There is also evidence that these PDH-isoforms are differentially distributed in visual eyestalk ganglia (e.g.…”
Section: Crustacean Hyperglycaemic Hormone (Chh)mentioning
confidence: 99%
“…However, notably, for hatching larvae released from intertidal or DVM-performing crabs circatidal rhythm components are certainly more important (193)(194)(195). detected in the crabs Callinectes sapidus (206), Cancer borealis (207,208) and Cancer productus (140), the shrimps Litopenaeus japonicus (209) and Litopenaeus vannamei (210), the crayfish Orconectes limosus (211), and the lobster H. americanus (207). In the CNS of diverse crustacean species, multiple neurosecretory and interneurons express PDHs (137,138,140,141,152), but innervation of the sinus gland as known e.g.…”
Section: Crustacean Hyperglycaemic Hormone (Chh)mentioning
confidence: 99%
“…Two other neurohemal structures, called the postcommissural and the pericardial organs, receive projections from NSCs in the brain and ventral nerve cord. A large variety of neuropeptides influencing pigmentation, carbohydrate levels, osmoregulation, growth/molting, and reproduction are released from each of these sites (Bulau et al 2004, Serrano et al 2004.…”
Section: Neuroendocrine System Of Arthropodsmentioning
confidence: 99%
“…Asterisk indicates dorsal arborizing dendrites (see D for orientation). Scale bar ¼ 100 lm in A; 50 lm in D-H; 25 lm in F,G; 20 lm in B and inset to C. Klein et al, 1994;Desmoucelles-Carette et al, 1996;Yang et al, 1999;Bulau et al, 2004). Notably, a recent report (Hsu et al, 2008) has convincingly demonstrated a differential distribution of b-PDH-I and -II isoforms in the eyestalk of Cancer productus, indicating that the former is likely to function as a neurotransmitter/modulator, whereas the latter functions as a neurohormone, and is only expressed by neurons that terminate in the SG.…”
Section: Discussion An Unusual Pdh In Eurydice Pulchramentioning
confidence: 97%